Computer-aided process design tools for debottlenecking a batch pharmaceutical production - Jully, Tan (2008)
The main objective of this work is to model and to debottleneck a batch pharmaceutical production with computer-aided process design (CAPD) and simulation tools. An eye drop production case study is firstly modelled based on a pharmaceutical production plant. Throughput analysis is next utilised to identify process bottlenecks that limit the increase of production and to evaluate different debottlenecking schemes. Scheme 1 considers an effort to maximise process throughput for a single batch operation, while Schemes 2 and 3 explore the possibility of minimising combined utilisation value of the process bottleneck. With the increase of batch throughput, installation of a new labelling process and the addition of an intermediate tank, Scheme 3 is identified as the debottlenecking scheme that achieves the increased production demand of 25%.